Knowledge Dissemination in the Long Nineteenth Century. European and Transatlantic Perception. Edited by Marina Dossena and Stefano Rosso - Sara Corrizzato (Iperstoria, 2018)
Review of the essay collection Knowledge Dissemination in the Long Nineteenth Century. European and Transatlantic Perception, edited by Marina Dossena and Stefano Rosso.